Comparison of Education and Episodic Memory as Modifiers of Brain Atrophy Effects on Cognitive Decline: Implications for Measuring Cognitive Reserve. (18th May 2021) - Mungas, Dan; Fletcher, Evan; Gavett, Brandon E.; Widaman, Keith; Zahodne, Laura B.; Hohman, Timothy J.; Mayeda, Elizabeth Rose; Dowling, N. Maritza; Johnson, David K.; Tomaszewski Farias, Sarah
Abstract: Objective: This study compared the level of education and tests from multiple cognitive domains as proxies for cognitive reserve. Method: The participants were educationally, ethnically, and cognitively diverse older adults enrolled in a longitudinal aging study. We examined independent and interactive effects of education, baseline cognitive scores, and MRI measures of cortical gray matter change on longitudinal cognitive change. Results: Baseline episodic memory was related to cognitive decline independent of brain and demographic variables and moderated (weakened) the impact of gray matter change. Education moderated (strengthened) the gray matter change effect. Non-memory cognitive measures did not incrementally explain cognitive decline or moderate gray matter change effects. Conclusions: Episodic memory showed strong construct validity as a measure of cognitive reserve. Education effects on cognitive decline were dependent upon the rate of atrophy, indicating education effectively measures cognitive reserve only when atrophy rate is low. Results indicate that episodic memory has clinical utility as a predictor of future cognitive decline and better represents the neural basis of cognitive reserve than other cognitive abilities or static proxies like education.